Between desire and perfection - Hurtado Madrigal, Roberth (2016)
The study of religious movements in the Middle Ages is a valuable point of analysis since Catholic Christianity was imposed hegemonic forms of knowledge in European societies in this period. This story is to analyze the medieval Languedoc immersed within the socio-political and religious processes 12th century and the first half of 13th, ie, an approach to governing daily life in occitania attempts in that period. The political events that altered the development of the Cathar religious movement within the Occitan society to comply with collective minds of society in one of its socio-political and units (Toulouse) were observed. Through a female character this particular company while the woman is rescued as an active social actor against the typical image of obedience and chastity that remains of the study period are explored.